Hemorrhagic Shock and Infantile Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The clinical characteristics, treatment and possible causes of hemorrhagic shock and encephalopathy in infants are described and a 5-month-old patient is reported from the Section of Neurology, The Children's Mercy Hospital, Kansas City, MO.